Unveiling the Landscape of Social Media Marketing Research: A Comprehensive Bibliometric Analysis - Lama, Padam Bahadur; Kharel, Shreekrishna; Pant, Ganesh Datt; Karki, Murari; Bhatta, Nirjana (Nepal Journal of Multidisciplinary Research, 2025)
Background: Social media marketing emerged as an effective business strategy that provides a sustainable foundation for customer involvement, interaction, and market development. The marketing endeavor through social media enables targeting potential customers, assessing the preferences of clients, and making informed decisions to foster effective promotion. Thus, this study attempts to analyze the recent trends and evolution in social media marketing research and to depict the pathway for future research. Methods: Social media marketing research was conducted utilizing a comprehensive bibliometric analysis with Biblioshiny and VOS Viewer software. This study covered the period 2010–2024, including 784 databases from Web of Science. Social media marketing was the main keyword and it included only research articles published in the English language containing business and economics as research subject areas and business and management as Web of Science categories. Results: The findings of the study revealed an increasing trend in scientific publications in the field of social media marketing. Moreover, the three-field plot depicted social media marketing as the leading keyword and most relevant source in the study, according to the Journal of Research in Interactive Marketing, indicating the highest source's local impact. Similarly, the most relevant author was Anderson, followed by Sanak-Kosmowska, and the most relevant affiliation was the American Marketing Association. Next, a leading country as the corresponding author's country was the United States of America (USA), followed by India, showing the USA as the highest contributor in scientific production and the most cited country. In addition, the article by Kozinets was the most globally cited document, and the work by Godey was the most locally cited document. Finally, the most frequent words were "social media marketing" in the study as a major theme. Conclusion: This research highlights current trends and future research directions in social media marketing, providing a strategic pathway for businesses and researchers. Novelty: This research measures the trends and direction and provides a future pathway in the social media marketing field. Further, it serves as an indispensable resource for research scholars and practitioners to unveil the social media marketing trends.